Pengaruh Kualitas Layanan dan Brand Image terhadap Kepuasan Pelanggan Lion Parcel di Kota Cirebon - Galih Maulana; Misbak Misbak (Journal of Economics and Management Scienties, 2026)
This study aimed to analyze the influence of service quality and brand image on customer satisfaction of Lion Parcel in Cirebon City. The research employed a quantitative approach with an associative design. The population consisted of all Lion Parcel customers in Cirebon City, with 35,662 delivery transactions recorded during February–April 2024. The sample was determined using the Slovin formula, resulting in 100 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed with SPSS through validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination analyses. The results indicated that service quality had a positive and significant effect on customer satisfaction, with a regression coefficient of 0.207 and a significance value of 0.000. Brand image also had a positive and significant effect on customer satisfaction, with a regression coefficient of 0.415 and a significance value of 0.000. Simultaneously, service quality and brand image significantly influenced customer satisfaction, as indicated by an F-value of 23.210 and a significance value of 0.000. The coefficient of determination (R²) was 0.324, indicating that both variables explained 32.4% of the variation in customer satisfaction. These findings highlight the importance of improving service quality and strengthening brand image to enhance customer satisfaction at Lion Parcel.